The Italian letter how the Bush administration used a fake letter to build the case for war in Iraq - Eisner, Peter 1965- (Rodale, 2007)
This account by two award-winning investigative reporters tracks the story of the forged intelligence document that the Bush administration used to push the nation into war with Iraq. It traces the road to war by following the scandal surrounding the Italian Letter, a fraudulent intelligence document that cooked up proof that the African country of Niger was prepared to supply Saddam Hussein with uranium for nuclear weapons. In the first book to uncover the details of a scandal bigger than the Iran-Contra affair, the authors have drawn on their unique access to a large group of CIA, FBI, and international sources as well as whistle-blowers. As frustration over Iraq continues to mount, this timely narrative provides fresh insights for a nation hungry for greater understanding of the manipulated intelligence document that altered the course of contemporary history.--From publisher description.
Includes bibliographical references and index
Keywords: Geschichte; Außenpolitik; Politik; Iraq War, 2003- -- Causes; Political corruption -- United States; Kriegseintritt; Begründung; Fälschung; Golfkrieg -- 2003; USA; United States -- Politics and government -- 2001-; United States -- Foreign relations -- 2001-